El nuevo horizonte económico argentino - Gambarotta, Héctor (América Latina Hoy, 2009)
RESUMEN: Gambarotta hace un repaso de los diferentes esquemas de gestión gubernamental de las últimas décadas en Argentina, para después hacer un balance de resultados económicos para este país y de los temas actuales más conflictivos: el desempelo, la lenta desregulación del sistema financiero local y el reducido nivel de capital doméstico. ABSTRACT: Gambarotta checks the different paths of the government management in Argentina during the last decades, and after he makes a balance of economical outcomes for this country and of the main issues in this moment: unemployement, the slow desregulation of local financial system and the small level of domestic capital.